Answer:
Step-by-step explanation:
The answer is 56 mph
Answer:
Answer to Let Bold Upper A equals Start 3 By 3 Matrix 1st Row 1st Column 1 2nd ... 1st Column 4 2nd Column 7 3rd Column 0 3rd Row 1st Column negative 4 ...
Step-by-step explanation:
Answer:
You would use > and <, if the first number is greater than the other, you would use >, and vice versa. For the others, you would write the numbers in the order stated, for example, 0, 5, and -7 would be written as -7, 0, 5, -7 being the smallest number, and 5 being the biggest number. Hope this helps.
Answer:
1: <
2: >
3: <
4: <
5: >
6: >
7: _-7_0_5_
8: _-10_3_10_
10: _-1/2_-8_0_1/2
There are the answers, the only one im not sure about is 10
Answer:
you hold the bowl with your thumb on the rim and then support it on the side with the rest of your fingers
Step-by-step explanation:
plz vote brainliest
The question is incomplete, the complete question is below:
Scientists have found a relationship between the temperature and the height above a distant planet's surface. , given below, is the temperature in Celsius at a height of kilometers above the planet's surface. The relationship is as follows: T(h) = 30.5 -2.5h.
a) Calculate T^-1(x)
b) T^-1(15)
Answer:
a)
b) 6.2 °C
Step-by-step explanation:
a)
b)
Which of these is logically equivalent to the given statement? (1 point)
1. If Amelia did not go to the park, then she did not finish her homework.
2. If Amelia did not finish her homework, then she will go to the park.
3. If Amelia goes to the park, then she did not finish her homework.
4. If Amelia finishes her homework, then she cannot go to the park.
Hello there.
In this problem, we can use our intuition of logic, but I will show a proof of the result in a truth table later. Then, let's get started!
Given:
→ Amelia finishes the homework (sentence H, can be True or False)
→ Amelia goes to the park (P, true or false)
Then, we have: If H, then P. Logically:
H ⇒ P
Then we can think: everytime she does the homework, she goes to the park. Therefore, if she did not go to the park, she will not have finished the homework (It is an equivalent sentence).
Alternative 1.
==========
Now, let's prove that (H ⇒P) is equivalent to (¬P ⇒ ¬H), via the truth table:
H P ¬H ¬P (H ⇒ P) (¬P ⇒ ¬H)
T T F F T T
T F F T F F
F T T F T T
F F T T T T
As we can see, the results are identical, therefore, the sentences are indeed equivalent.
I hope it hepls :)
Answer:
The graph is shown below.
=========================================================
Explanation:
Notice that if we multiplied the denominator (x-1) by 5, then we get 5(x-1) = 5x-5.
This is close to 5x-7, except we're off by 2 units.
In other words,
5x-7 = (5x-5)-2
since -7 = -5-2
Based on that, we can then say,
This answer can be reached through alternative methods of polynomial long division or synthetic division (two related yet slightly different methods).
-------------------------
Compare the equation to the form
We can see that
The vertical asymptote is x = 1, which is directly from the h = 1 value. If we tried plugging x = 1 into g(x), then we'll get a division by zero error. So this is why the vertical asymptote is located here.
The horizontal asymptote is y = 5, which is directly tied to the k = 5 value. As x gets infinitely large, then y = g(x) slowly approaches y = 5. We never actually arrive to this exact y value. Try plugging in g(x) = 5 and solving for x. You'll find that no solution for x exists.
The point (h,k) is the intersection of the horizontal and vertical asymptote. It's effectively the "center" of the hyperbola, so to speak.
The graph is shown below. Some points of interest on the hyperbola are
Another thing to notice is that this function is always increasing. This means as we move from left to right, the function curve goes uphill.